Molecular Cloning and Functional Analysis of the NPR1 Homolog in Kiwifruit (Actinidia eriantha) - Sun, Lei-Ming; Fang, Jin-Bao; Zhang, Min; Qi, Xiu-Juan; Lin, Miao-Miao; Chen, Jin-Yong (Frontiers in Plant Science, 2020)
Kiwifruit bacterial canker, caused by the bacterial pathogen Pseudomonas syringae pv. actinidiae (Psa), is a destructive disease in the kiwifruit industry globally. Consequently, understanding the mechanism of defense against pathogens in kiwifruit could facilitate the development of effective novel protection strategies. The Non-expressor of Pathogenesis-Related genes 1 (NPR1) is a critical component of the salicylic acid (SA)-dependent signaling pathway. Here, a novel kiwifruit NPR1-like gene, designated AeNPR1a, was isolated by using PCR and rapid amplification of cDNA ends techniques. The full-length cDNA consisted of 1952 base pairs with a 1,746-bp open-reading frame encoding a 582 amino acid protein. Homology analysis showed that the AeNPR1a protein is significantly similar to the VvNPR1 of grape. A 2.0 Kb 5′-flanking region of AeNPR1a was isolated, and sequence identification revealed the presence of several putative cis-regulatory elements, including basic elements, defense and stress response elements, and binding sites for WRKY transcription factors. Real-time quantitative PCR results demonstrated that AeNPR1a had different expression patterns in various tissues, and its transcription could be induced by phytohormone treatment and Psa inoculation. The yeast two-hybrid assay revealed that AeNPR1a interacts with AeTGA2. Constitutive expression of AeNPR1a induced the expression of pathogenesis-related gene in transgenic tobacco plants and enhanced tolerance to bacterial pathogens. In addition, AeNPR1a expression could restore basal resistance to Pseudomonas syringae pv. tomato DC3000 (Pst) in Arabidopsisnpr1-1 mutant. Our data suggest that AeNPR1a gene is likely to play a pivotal role in defense responses in kiwifruit.